Qualidade de vida no trabalho de profissionais no ambiente escolar: oficinas de ginástica laboral para os servidores do Instituto Federal de Alagoas – Campus Coruripe - Santos, Josimar Barbosa dos (2023)
This research approaches labor gymnastics as a practice of physical exercises in the work environment, its benefits in the prevention of occupational diseases and promotion of greater physical and emotional well-being of workers. The aim of this study was to verify the benefits of labor gymnastics in the quality of life at work of employees of the Federal Institute of Alagoas - Campus of Coruripe, with regard to the reduction of pain and body discomfort. The level of physical activity and sedentary behavior of employees was identified, as well as feeling of discomfort/body pain before and after labor gymnastics workshops. Thus, the formative and bodily needs of participants, related to the theme addressed, were better met by labor gymnastics workshops, which had their stages documented using photographic record and note, the basis for the elaboration of an educational product capable of guiding future applications of workshops. This study is of quali-quantitative nature and its development took place through action research, in which participants were active agents of decisions made. The sample consisted of 38 participants selected in a simple casual way, based on confidence level of 90% and margin of error of 6%. Data were collected through questionnaires virtually applied: international physical activity questionnaire – short version (Appendix A) and the discomfort/body pain questionnaire (Appendix B). Data were treated through descriptive statistical analysis and tabulated using Excel spreadsheet. It was found that only 50% practiced weekly at least 150 minutes of moderate physical activity and only 18% practiced weekly at least 75 minutes, showing that the vast majority of the sample reached levels below those recommended by WHO for adults. With regard to sedentary behavior, 50% spend 8 hours or more sitting or lying down during the week and at the end of the week, 55% spend 8 hours or more sitting or lying down. In addition, at the initial diagnosis, 75% indicated discomfort/pain in 5 or more body regions (in different degrees). In the comparative analysis of discomfort/body pain data from the application and reapplication of the questionnaire, 43.5% had reduction, 43.5% had increase and for the remaining 13%, there was maintenance of levels of discomfort/body pain. The actions of the present dissertation provided, in addition to formative experiences inherent to labor gymnastics and related ones, moments of education in health promotion and actions to encourage a more physically active lifestyle. It is hoped that this production will help to make the issue of quality of life at work even more academically evident, which is something extremely relevant to achieving improvements in the work environments of educational institutions in our country.